Enrichment in ascorbic acid of the rotifer Brachionus plicatilis O.F. Müller for the rearing of marine fish larvae - Planas, Miguel; Carnero, D. G.; Munilla-Morán, Roberto; Merchie, G.; Lavens, P. (Universidad de Barcelona, 1995)
6 pages, 4 figures, 2 tables.-- Actas del V Congreso Nacional de Acuicultura, Sant Carles de la Ràpita, 10-13 Mayo 1995 [EN] The aim of this work was to establish a laboratory tool to permit rapid progress towards quantification of the requirement for ascorbic acid (AA) in marine fish larvae during the early feeding period. As a first step rotifers only differing in their AA levels were successfully produced. The biochemical and enzymatic composition of this organism remained stable in clear seawater for, at least, 24 hours. Therefore they were considered suitable for increasing A levels in turbot larvae. The AA level of the larvae was positively correlated with the AA content of the rotifer used. This demonstrates that AA was successfully incorporated in the larvae [ES] El objetivo de este trabajo fue desarrollar una técnica que permitiera estudiar el requerimiento de ácido ascórbico (AA) en larvas de peces marinos durante las fases iniciales de alimentación. En primer lugar, se desarrolló una técnica de enriquecimiento de rotíferos que permitió obtener distintos niveles de AA en la presa, sin observarse cambios en su composición bioquímica ni en su equipamiento enzimático 24 horas después de ser transferidos a agua limpia. Por tanto, la utilidad de la técnica utilizada se consideró satisfactoria. La utilización de estos rotíferos con larvas de rodaballo puso en evidencia una incorporación eficiente de la vitamina en las larvas, ya que el nivel de AA en estas estuvo directamente relacionado con el nivel de la vitamina en las presas European Community, project no. AIR2-CT93-1449 (DG IX SSMA) No